Zastosowanie wielowymiarowej analizy porównawczej do oceny zaspokajania potrzeb mieszkaniowych w warunkach zmieniającej się koniunktury gospodarczej - Zapotoczna, Marcelina; Sujkowski, Zbigniew (The Use of Multi-Dimensional Comparative Analysis to Assess the Fulfillment of Public Housing Needs in Conditions of Changing Economic Situation, 2009)
A housing branch is one of the key element of economy. It relates both to the macroeconomic as well as social aspect of economy, and is measured with the degree of fulfillment of the public housing needs. The authors analyze the housing investment mechanism that drives economy using the multidimensional comparative analysis. They do so in order to evaluate the degree to which the public housing needs are met after Poland became the member of the European Union. The analysis includes nine explanatory variables which are relevant to the problem under investigation. This impact on the sector's effectiveness is possible to detect using macroeconomic housing indices. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 39, T. 1, s. 912-920